Biological Low-voltage Scanning Electron Microscopy. - Pawley, James (Springer, 2007)
Major improvements in instrumentation and specimen preparation have brought SEM to the fore as a biological imaging technique. In FESEM, a field-emission cathode placed in the electron gun of a scanning electron microscope provides narrower probing beams and high electron energy. The result is improved spatial resolution and minimized sample charging and damage. Images produced are less destroyed and have a spatial resolution down to 1.5 nm, three to six times better than conventional SEM. Although this imaging technique has undergone tremendous developments, it is still poorly represented in.